2017
DOI: 10.1136/annrheumdis-2017-211290
|View full text |Cite
|
Sign up to set email alerts
|

Germinal centres in diagnostic labial gland biopsies of patients with primary Sjögren’s syndrome are not predictive for parotid MALT lymphoma development

Abstract: Presence of GCs in labial gland biopsies does not differ between patients with pSS that develop parotid MALT lymphoma and patients with pSS who do not develop lymphoma. The presence of GCs in labial gland biopsies is therefore not a predictive factor for pSS-associated parotid MALT lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
2
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 19 publications
1
44
2
6
Order By: Relevance
“…However, importantly, only one of the seven non-Hodgkin lymphomas observed in the pSS cohort of the study of Theander et al 12 was a parotid MALT lymphoma, that is, the type of lymphoma that is characteristically associated with pSS. In our retrospective study,2 we could not demonstrate that the presence of well-defined germinal centres in diagnostic minor salivary gland biopsies (both H&E and Bcl-6-defined) was also predictive for the development of parotid MALT lymphoma. We agree with Alunno et al 1 that histopathological analysis of salivary gland biopsies from larger cohorts of patients scored using standardised protocols and with well-defined definitions are needed to assess the clinical relevance of the presence of germinal centres in salivary gland biopsies of patients with pSS.…”
contrasting
confidence: 82%
See 3 more Smart Citations
“…However, importantly, only one of the seven non-Hodgkin lymphomas observed in the pSS cohort of the study of Theander et al 12 was a parotid MALT lymphoma, that is, the type of lymphoma that is characteristically associated with pSS. In our retrospective study,2 we could not demonstrate that the presence of well-defined germinal centres in diagnostic minor salivary gland biopsies (both H&E and Bcl-6-defined) was also predictive for the development of parotid MALT lymphoma. We agree with Alunno et al 1 that histopathological analysis of salivary gland biopsies from larger cohorts of patients scored using standardised protocols and with well-defined definitions are needed to assess the clinical relevance of the presence of germinal centres in salivary gland biopsies of patients with pSS.…”
contrasting
confidence: 82%
“…Bcl-6 is consistently expressed at high levels by germinal centre B-cells and is commonly applied by pathology laboratories for lymphoma subtyping. In our study,2 we observed slightly more germinal centres in Bcl-6 stained sections of pSS salivary gland biopsies compared with H&E stained sections, which was due to the fact that also small germinal centres (defined as clusters of > 5 Bcl-6 + B-cells) could easily be detected. Larger cohorts of salivary gland biopsies are obviously needed to establish the higher sensitivity and specificity of Bcl-6 stained sections, compared with H&E salivary gland stained sections.…”
mentioning
confidence: 40%
See 2 more Smart Citations
“…We read with interest the article by Haacke et al 1 demonstrating that the presence of germinal centres (GCs) in minor salivary glands (MSG) of patients with primary Sjögren’s syndrome (pSS) does not differ between subjects developing non-Hodgkin’s lymphoma (NHL) and those who do not develop this complication. In recent years the prognostic role of MSG histopathology has been a matter of intense debate.…”
mentioning
confidence: 99%